The Assessment of Ventricular Arrhythmia Indicators Based on Electrocardiography in Patients With Differentiated Thyroid Cancer Followed Up With Levothyroxine Suppression. (August 2021) - Hepsen, Sema; Sakiz, Davut; Pamukcu, Hilal Erken; Arslan, Ismail Emre; Duger, Hakan; Akhanli, Pinar; Sencar, Muhammed Erkam; Unsal, Ilknur Ozturk; Ucan, Bekir; Kizilgul, Muhammed; Cakal, Erman
Levothyroxine suppression therapy (LST) can cause some unfavorable effects on the cardiovascular system in patients with differentiated thyroid cancer (DTC). The aim of this study was to evaluate ventricular arrhythmia predictors based on electrocardiography (ECG) in patients with DTC with LST. The ECG parameters including QT, corrected QT (QTc), Tp-e intervals, Tp-e/QT, and Tp-e/QTC ratios of 265 patients with DTC who met the inclusion criteria were compared with 100 controls. No difference was observed in the number of patients with DTC and controls with prolonged and borderline QTc interval ( P = .273). Tp-e interval, Tp-e/QT, and Tp-e/QTc ratios were significantly higher in patients ( P = .002, P = .02, P = .003; respectively). Linear regression analysis suggested that male gender was a predictor of higher Tp-e interval, Tp-e/QT, and Tp-e/QTc ratios (β = 4.322, R 2 = 0.024, P = .042; β = 0.016, R 2 = 0.048, P = .005; β = 0.015, R 2 = 0.044, P = .006, respectively). A higher serum fT4 level was found to be associated with a higher Tp-e/QT ratio (β = 0.018, R 2 = 0.089, P = .007). Ventricular arrhythmia indicators were found to be higher in patients with DTC with LST. Defining ventricular arrhythmia predictors through ECG, an easily accessible cardiac diagnostic tool, can be potentially useful in raising awareness of the possible cardiac harm of LST.